The Effect of Conditional Cash Transfer on Temptation Goods Consumption: Evidence From Program Keluarga Harapan in Indonesia - Simanjuntak, Bonar Partungkoan; Jinnai, Yusuke (Jurnal Penelitian Kesejahteraan Sosial, 2021)
Conditional Cash Transfer (CCT) has become a popular policy utilized by governments in many countries to serve as a safety net for low income people. However, several previous studies find that the increase of income from CCT will increase the consumption of temptation goods. This study examines the effect of Program Keluarga Harapan, a CCT policy in Indonesia, to the consumption of temptation goods. By utilizing fixed effect model, this study finds that the increase of every rupiah decreases tobacco consumption. This study contributes to the literature by estimating the rupiah value of CCT.